Glycaemicparameters, Dyslipidaemia and Thyroid Hormone: An exploratory study of their interrelationship in Type 2 Diabetes Mellitus patients - Sharma, Shrikant; Mathew, Don; Kumar Sharma, Ashish; Pal Singh, Suraj; Sankhla, Vasudev; Bhatia, Neelam; Sahi, Disha (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus and thyroid disorders may coexist and impacting each other. The thyroid gland function (hypo- and hyper-function) may affect the metabolism of carbohydrates. Both conditions have an impact on the lipid profile since insulin resistance or insufficiency alters important enzymes and pathways involved in lipid metabolism. Lipid abnormalities are common in diabetes mellitus. The purpose of this study is to determine how diabetes mellitus, hypothyroidism, and dyslipidaemia are related. Method: The study included 300 participants, 150 of whom were healthy controls and 150 of whom had diabetes mellitus and hypothyroidism. 150 people with diabetes were further divided into 75 people who had dyslipidemia and 75 people who did not. Serum lipid profiles and blood sugar levels were measured using the Mindray BS240 analyzer. Triiodothyronine [T3], thyroxine [T4], and thyroid stimulating hormone [TSH] were measured using chemiluminescence immunoassay. Result: The study found that female subjects with diabetes had a higher prevalence of dyslipidaemia. The TSH differences between the study and control groups were more significant (OR 3.147, P Value0.001*). Notable were the T4 (OR 1.734, P Value0.001*) and T3 (OR 2.031, P Value0.001*), mean differences as well. Higher levels of FBS, PPBS, and RBS were observed. The lipid profile total cholesterol (OR 3.120, P Value0.001*), triglycerides (OR 1.592, P Value0.001*), HDL (OR 2.173, P Value0.001*), LDL (OR 2.110, P Value0.001*), and VLDL (OR 2.194, P Value0.001*) is also significant compared to controls. Conclusion: This study shows that T2DM significantly affect thyroid function especially in female. It is crucial to take thyroid function into account in diabetic patients because changes in thyroid hormone levels may be caused by insulin resistance and altered glucagon levels.The results suggest a significant association between hypothyroidism and diabetes with dyslipidaemia.